Houses by the sea - Graffin, Emmanuelle (New York, N.Y. : Thames & Hudson, 2011)
This book showcases thirty-three exceptional houses from around the world in a variety of styles, from traditional to contemporary. Each house has its own ambiance and its own particular relationship with the environment, whether it is perched on top of a cliff, nestled in a rocky hollow, or built on the sand. Both inside and out and in every locale, the design approaches range from simple rustic style to the ultimate in luxurious elegance.
Includes bibliographical references (p. [221]).
Keywords: Seaside architecture; Architecture, Domestic